Proses Pemahaman Pembuatan Ketupat Pada Pelaksanaan Upacara Agama Hindu Di Sindu Cakranegara Mataram - Dewi, Ni Luh Sinar Ayu Ratna; Patni R, Gusti Ayu Santi; Saridewi, Desak Putu; Listiawati, Ni Putu; Zaenab, Siti; Yadnya, Made Sutha (Universitas Mataram, 2024)
Community service activities are carried out in providing simple knowledge and understanding of the concept of local wisdom in the implementation of religious activities. The selection of the venue for the Ida Pedanda Nyoman Sebali Keniten Mangkuh Ceremony will be held on Thursday, September 19, 2024. The main thing that is socialized in this is to use the form of the meaning function of the ketupat, with the existence of the birth ketupat which is identical to the food of local wisdom, from various customs and customs or traditions. The annual tradition carried out by the majority of the population of Indonesia, namely the Eid al-Fitr tradition community, the Eid al-Fitr tradition is one of the traditions that usually occurs in the community, the Muslim community. This is a harmony that needs to be studied and revealed in order to have the right understanding. The result of this service is open insight in religious moderation, tolerance, and harmony in sitting together to make ketupat.